Analisis Risiko Operasional pada Perusahaan Benih Jagung PT. Giri Agro Raya Sejahtera - Islami, Nabila; Fauziyah, Elys; Wijayanti, Dian Eswin (LP3M Universitas Putra Bangsa, 2025)
Corn is a key food sector that plays an important role in boosting the economy in Indonesia. Madura, as one of the largest corn-producing regions in East Java, continues to strive for corn self-sufficiency through the provision of superior corn seeds. PT. Giri Agro Raya Sejahtera (PT. GARS) is an agricultural company in Madura that produces high-quality corn seeds of the Madura-3 variety. As a newly established company, PT. GARS still faces limitations in its risk planning. The company has experienced several unexpected events related to its operational system, resulting in losses. The aim of this study is to identify sources of risk and analyze the level of risk at PT. GARS. The research methods used are the Fishbone Diagram and Failure Mode and Effect Analysis (FMEA). The data were obtained through interviews with key informants, consisting of one company director, one processing manager, one marketing manager, and one marketing staff member. Based on the fishbone diagram, five types of risks were identified: (1) human resource risks, including occupational health and safety as well as human behavior; (2) production risks, including planting, maintenance, and harvesting; (3) technological risks, consisting of equipment availability and technological mastery; (4) process risks, which involve seed processing and seed quality testing; and (5) external risks, including weather, pest and disease attacks, competitors, and distribution. Based on the Risk Priority Number (RPN), two sources of risk with high risk levels are process risks in seed processing and external risks, particularly unpredictable weather.